Setal Morphology of the Feeding Apparatus of Three Sesarmid Crabs (Crustacea: Decapoda Grapsoidea) from Brazil - Turini, Tassia [UNESP]; de Araujo Pereira, Francinilda [UNESP]; Lima, Janaína [UNESP]; Perazzi, João Pedro [UNESP]; Lupino, Livia Martins [UNESP]; Colavite, Jessica; Santana, William [UNESP] (Springer Nature, 2024)
Here, we describe the morphology of the setal types of the feeding apparatus (mandible, maxillule, maxilla, first to third maxillipeds and the cheliped) of three species of sesarmid crabs, Aratus pisonii, Armases angustipes and Sesarma rectum, using scanning electron microscopy (SEM) techniques. The setal types previously identified encompass pappose, plumose, plumodenticulate, serrated, simple, and cuspidate, each with its own distinct subtypes. Three different types of setae are described and named here: capitate, cluster serrated, and scopa setae. The three species’ mouthparts are very similar, but Aratus pisonii has some marked differences, being the only species to have capitate setae on the first maxilliped, base and coxa of the maxilla and maxillule, and mandibular palp, plumodenticulate setae in the mandibular palp and tufts of cluster serrated setae in the chelipeds. Because it is considered the most herbivorous species among those studied, such differences possibly relate to the feeding habits.
Keywords: Feeding Appendages; Feeding Structures; Morphology; SEM; Setae